Formation of SiC by radiative association - Andreazza, C. M. [UNESP]; Vichietti, R. M. [UNESP]; Marinho, E. P. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Rate coefficients for radiative association of silicon and carbon atoms to form silicon carbide molecule (SiC) are estimated. The radiative association of Si(3P) and C(3P) atoms mainly occurs through the C3 Pi state followed by radiative decay to the X3 Pi state. For the temperature range of 300-14 000 K, the rate coefficients slowly increase with temperature and they can be expressed by K(T) = 2.038 x 10-17(T/300)-0.01263 exp(-136.73/T) cm3 s-1.
Keywords: atomic data; atomic process; circumstellar matter; ISM: molecules